Sexual selection across sensory modalities: female choice of male behavioral and gustatory displays. (6th June 2018) - Berson, Jacob D; Simmons, Leigh W
Abstract : Female dung beetles prefer males that court vigorously and smell different to the average male. Males of many species have traits that influence the likelihood of being accepted as a mate by females. Previous work on bull-horned dung beetles revealed that males who courted more vigorously were more successful in securing a mating. Here, we show that independently of courtship activity, chemicals on the cuticle of this species also contribute to male mating success. Abstract: The role of cuticular hydrocarbons in sexual displays has received considerable interest over the last two decades. For example, multiple studies have documented significant directional and nonlinear sexual selection acting on the cuticular hydrocarbon profiles of both male and female insects. The majority of these studies have excluded other sensory modalities that may influence attractiveness and measured selection using laboratory raised individuals. Furthermore, much of this work has been conducted using drosophilid fruit flies and crickets, and investigations using different taxa are necessary to improve our understanding of broader taxonomic trends. Here, we extend our understanding of sexual selection on cuticular hydrocarbons by measuring selection imposed by female mate choice on male bull-horned dung beetles, Onthophagus taurus . Both male and female beetles used in our study were collected from the field, ensuring that our estimates of selection incorporated some degree of naturally occurring variation in both cuticular hydrocarbon profiles and female mate preferences. Consistent with previous studies on this species, we found significant directional selection on male courtship displays. We also found significant nonlinear selection on the male cuticular hydrocarbon profile acting independently of the influence of behavioral courtship. Our data are consistent with a role for cuticular hydrocarbons in the mating system of this species and suggest that female O. taurus use multiple sensory modalities to assess different aspects of male quality.